Globalisation and the transformation of the tax state - Philipp Genschel (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
How does globalisation affect taxation? The academic wisdom is split on this question. Some argue that globalisation spells the beginning of the end of the national tax state while others maintain that it hardly constrains tax policy choices at all. This paper comes down in the middle. It finds no indication that globalisation will fatally undermine the national tax state, but still maintains that national tax policy is affected in a major way. The effect is not so much to force change upon the tax state as to reduce its freedom for change. Comparing the first three decades of the twentieth century to the last three decades, it is remarkable how much change and innovation there was then and how much incrementalism and stasis there is today. – – Welchen Einfluss hat die Globalisierung auf die nationale Steuerpolitik? In der Politikwissenschaft gehen die Meinungen auseinander. Manche fürchten, die Globalisierung bedeute den Anfang vom Ende des Steuerstaates. Andere hingegen meinen, die nationale Steuerautonomie werde durch die Globalisierung kaum eingeschränkt. Die Wahrheit, so vermutet dieser Beitrag, liegt in der Mitte. Es gibt keinen empirischen Hinweis, dass die Lebensfähigkeit des Steuerstaates fundamental in Frage gestellt würde. Trotzdem bleibt er vom Globalisierungsprozess nicht unberührt. Der Effekt besteht nicht so sehr darin, den Steuerstaat zu Reformen zu zwingen, die dieser sonst nicht vorgenommen hätte. Der Effekt ist vielmehr, seine Reformspielräume generell zu verkleinern. Im historischen Rückblick fällt auf, wie viele heftige steuerpolitische Umbrüche es vor dem Einsetzen des verschärften Globalisierungsprozesses in den siebziger Jahren des 20. Jahrhunderts gab und wie wenige danach.
Keywords: 330; Steuerpolitik; Nationalstaat; Globalisierung; Standortwettbewerb; Welt